Integration of IoT and Machine Learning for Real-Time Monitoring and Control of Heart Disease Patients - Neelamadhab Padhy; Rasmita Panigrahi; Sibo Prasad Patro; Vishal Kumar Swain; Kiran Kumar Sahu (Proceedings)
Context: In the 21st century, the integration of IoT and AI plays a vital role in the real-time monitoring and control of heart disease [...]